Uporaba komplementarnih in alternativnih metod zdravljenja med polnoletnimi prebivalci Slovenije - Ivetić, Vojislav (Acta medico-biotechnica, 2013)
Purpose: The aim of our research was to determine how many people use complementary and alternative medicine (CAM) and how the use of CAM depends on the gender, age, education, and the living environment of each individual person. We wanted to determine the level of fondness for the providers of CAM and define the most popular alternative medicinal preparations. Methods: The cross-sectional study was based on an anonymous questionnaire sent to the houses of a randomly selected sample (N=1000) of adults from the Republic of Slovenia in April 2009. The sample was selected using the telephone book. The data was statistically analysed using the chi-square method and t-test, depending on the nature of the variables. Results: The survey was returned and answered correctly by 410 (41.0%) subjects. According to the results, complementary and alternative medicine was used by 9.0% of the subjects. The use of CAM was independent of age, gender, education, and the living environment. According to the point scale, homeopathy was trusted by 16.9% of people, followed by healers who were trusted by 11.0%. From a statistical point of view, homeopaths were much more trusted by people who had completed a secondary education. The most popular medicinal preparations were herbs and different types of tea (74.4%), followed by vitamins and minerals (69.0%). Homeopathic preparations were used by 4.6% of people. Conclusion: We confirmed a 9.0% presence of alternative medicine in Slovenia, not taking into account herbal medicines, treatments with herbal preparations or tea, and acupuncture. We also have established that 11.0% of the population trust healers and only 16.9% of the population trust homeopaths.
Keywords: alternative medicine; alternativna medicina; complementary medicine; healing practice; komplementarna medicina; trust; zaupanje; zdravilstvo